Ketidakpastian Hukum Pergantian Calon DPRD Terpilih: Ancaman terhadap Esensi Sistem Proporsional Terbuka (Studi Kasus Pemilihan Umum 2024 di Jawa Tengah) - La Ode Ibrah Haikal Rachman Kadir; Rodiyah (Annual Review of Legal Studies, 2025)
This study conducts a juridical analysis of legal uncertainty in the replacement of elected Regional Legislative Council (DPRD) candidates, specifically examining its threat to the essence of the open proportional electoral system in Indonesia. Drawing upon legal certainty theories, this research identifies ambiguities within Article 426 of Law No. 7 of 2017 on General Elections, particularly concerning the "resignation" clause and the potential for misuse under "failure to meet requirements". These legal loopholes grant political parties excessive discretion in candidate replacement. The manifestation of this uncertainty is evident in the 2024 General Election in Central Java, where specific cases of elected DPRD candidates were replaced based on pre-signed resignation letters. This practice, stemming from internal party strategies, led to the subsequent rejection of lawsuits by the State Administrative Court (PTUN) in Semarang, which further legitimized these formalistic interpretations, despite underlying substantive issues. This practice fundamentally undermines voter sovereignty and distorts the core principles of the open proportional system. It effectively negates voters' direct choices, transforming the de jure open system into a de facto party-controlled mechanism. Such inconsistencies erode the legitimacy of political representation and public trust in the electoral process, as highlighted by prior academic criticisms that remain unaddressed in legislative reforms. The study concludes with urgent recommendations for legislative amendments and enhanced regulatory oversight to ensure substantive legal certainty and protect citizens' fundamental political rights.